Complaint Management Analysis in Digital Transactions: a Case Study of Saqu Bank - Nur Annisa; Wahyudi David (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze customer complaint handling management at Bank Saqu Indonesia using the service quality dimension framework proposed by Mark Colgate (2018), namely Reliability, Responsiveness, and Relationship. The background of this study is based on the increasing importance of digital banking service quality in building customer satisfaction and loyalty in the era of financial transformation. The research method used is a qualitative case study approach. Data were collected through in-depth interviews with four external informants (customers) and one internal informant (the bank), then analyzed using NVivo12 software with thematic analysis techniques (Braun & Clarke, 2006). The analysis process included data familiarization, coding, theme identification, review, and thematic narrative development. The results showed that the most dominant customer complaints were related to the Reliability dimension, specifically delays in account verification, system errors, and lack of notification when disruptions occurred. The Responsiveness dimension was also highlighted, particularly the slow response of customer service to transaction problems. Meanwhile, the Relationship dimension emerged in the form of complaints related to the lack of personalized service and appreciation for existing customers. Internally, Bank Saqu already has a Jira-based complaint management system with a 24/7 Service Level Agreement (SLA), but still faces challenges in handling traffic spikes during promotional periods. This study concludes that effective complaint management requires an integration of system technical reliability, response speed, and strategies for building emotional relationships with customers. The contribution of this study lies in the development of a revised research framework that emphasizes the importance of simultaneously managing three dimensions of service quality to achieve Best Service Excellence in the digital banking sector.